EFFICIENCY AND COMPETITIVENESS OF BANK PERKREDITAN RAKYAT (BPR) IN THE BALI PROVINCE OF INDONESIA - Layyinaturrobaniyah .; Mokhamad Anwar; Ratna Komara; Sulaeman Rahman Nidar (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2019)
This study aims to estimate and test technical efficiency and conduct analysis on the competitiveness of BPRs in the Province of Bali for the period 2012-2016. Estimation on efficiency with the Data Envelopment Analysis (DEA) method was carried out on 134 BPRs whose data is obtained from OJK Regional Office 8 Bali and Nusa Tenggara. Meanwhile, to analyze competitiveness, a questionnaire was distributed to BPR customers, upon which data from customers is analyzed by Focus Group Discussion (FGD) together with BPR and OJK management as regulators. The Results of this study showed that in average, the technical efficiency of BPRs in Bali decreased from year to year from, i.e., 0.6581 in 2012 to 0.5993 in 2016. Buleleng Regency is listed as an area that has the most efficient BPRs with an average efficiency value of 0.7575, then followed BPRs from Karangasem Regency in second place with efficiency scores of 0.7184, and BPRs from Gianyar Regency in third place with a score of 0.6854. Further, based on the results of the analysis of competitiveness and from the FGD, it can be concluded that one of the strengths of BPRs in Bali Province is the loyalty of its customers.